Educação dialógica e democrática no centro integrado de educação de jovens e adultos CIEJA Perus I - Baldo, Aline Caroline (Universidade Federal de São Carlos, 2021)
Dialogical and democratic practices in the school space are relevant to an education that values students' rights and their critical, reflective and emancipatory training. Thus, this research aims to identify evidence, expressed and subliminal linguistic content of a dialogic and democratic education in the Blog of the Integrated Center for Youth and Adult Education, CIEJA PERUS I. The research theoretical framework is based on the understanding of this education from the Paulo Freire perspective, aiming at a comprehensive knowledge of dialogic and democratic education for the author. The research has a qualitative approach with an exploratory nature and appropriates the procedures of documental research, with analysis of the CIEJA PERUS I Blog, a document that informs about the institution and its pedagogical practices, thus seeking to verify whether what is exposed there goes to the meeting a dialogic and democratic education. The results of the present research allow us to conclude that there are signs of a dialogic and democratic education in the investigated school space, as we are faced with: the presence of the Crioula language on the Blog, in attention to Haitian students; the love and dialogue with the subjects included there, expressed in the work with technology and its importance in the critical and life transformation of these subjects; publications that refer to an integrative curriculum aimed at reflective and emancipatory projects in the relationship between educator and student, aimed at participatory and collaborative education. It is considered, therefore, that CIEJA PERUS I is a school according to the Blog, which encourages and promotes an education of subjects immersed in a dialogic and democratic education, with students at the center of the pedagogical practices promoted and debated.
Dialogical and democratic education in the center youth and adult education integrated CIEJA Perus
Keywords: Educação de jovens e adultos; CIEJA; Educação democrática; Pedagogia dialógica; Youth and adult education; CIEJA; Democratic education; Dialogical pedagogy; CIENCIAS HUMANAS::EDUCACAO